COMP-08. SURVIVING BY EXPLORING: COULD GLIOBLASTOMA CELLS FOLLOW THE THEORY OF EXPLORATORY ADAPTATION? - Celiku, Orieta (Neuro Oncol, 2018)
BACKGROUND: Glioblastoma (GBM) prognosis remains abysmal despite decades of research. Standard approaches to treatment target the tumor growth mechanisms, and novel ones attempt to better recruit the immune system. However, cancer has a remarkable ability to adapt, surviving the introduced stress signals and thriving in new microenvironment settings. Understanding these fundamental processes of adaptation, and mechanisms specific to GBM, would enable a robust treatment approach that considers how cells utilize compensatory mechanisms. METHODS: We adapted a recent theory of exploratory adaptation -- prescribing how small random perturbations to the regulatory network could be propagated to changes in the cellular phenotype -- to examine the question of how GBM cells adapt across their microenvironment. We studied the transcriptomic profiles of spatially-separated tumor anatomical structures using patient-derived data from the IVY Glioblastoma Atlas Project. First, we asked how exploratory adaptation might explain the ability of cells to change their phenotype given their initial anatomical location; second, we tested if tumor cells from one location can adapt over time to resemble cells in neighboring locations. RESULTS: We defined the cellular phenotype at the functional pathway activity level and introduced notions of phenotype similarity and convergence. We simulated the dynamics of the pathway activities while cells attempt to obtain the phenotypes of cells from a different spatial environment. We estimated the distribution of each pathway activity over time, and observed some transitions (for example, the sulfur metabolism pathway shifting from a unimodal to a bimodal distribution) suggestive of exploratory adaptation. Several DNA repair pathways, including mismatch repair and non-homologous end-joining increased their distribution spread over time. Some pathways reached the tested destination distributions, but the global phenotypes did not meet our convergence criteria. CONCLUSION: Our results suggest that exploratory adaptation could partially explain adaptation in GBM, but could not fully account for it.